FINANCIAL LITERATION: DETERMINANTS OF FINANCIAL WELL-BEING IN THE BATIK SMALL AND MEDIUM INDUSTRIES IN EAST JAVA - Sumani, Sumani; Roziq, Ahmad (Jurnal Aplikasi Manajemen, 2020)
The research objective is to examine the financial well-being of batik SMEs in East Java-based on financial literacy, namely: financial knowledge, financial attitudes, and financial behavior. The study population was SMEs Batik practitioners in East Java. The sampling technique used multistage sampling, the first step was to determine the area of research and then determine the batik SMEs of 125 respondents using census methods. Data analysis techniques using SEM-PLS. The results showed that financial knowledge has a significant effect on financial behavior, but financial knowledge has no effect on financial attitudes. Financial attitudes also do not affect financial behavior. Financial knowledge, financial attitudes, and financial behavior have a significant effect on the financial well-being of SMEs Batik. Future studies should be able to use proxies or other indicators for financial attitudes and do groupings based on the characteristics of batik SMEs such as education, length of business, family background, and training opportunities.